THE ENGLISH TEACHER’S PROFICIENCY IN SOUTH SULAWESI: ITS IMPLICATIONS TO THE TEACHER’S PERFORMANCE - Ishak Ishak (University of Kuningan, 2021)
In this article, it referred to the implications of proficiency to the teacher’s performance in the classroom in South Sulawesi. Most of English teachers associate level of language proficiency with greater powerful teaching performance skills. This research was descriptive qualitative research in South Sulawesi, the participants consisted of several qualified teachers aged from 30 – 40, and they have been teaching more than 10 years, all of the participants interviewed felt strong desire about the implications of proficiency. The data were collected from observation, interview and documents and it was analyzed in interpretation to draw inferences and conclusions based on the description data. The result of this research provided a great interpretation of proficiency and its excessive implication for teaching English, the higher level of language proficiency is, the better performance of the teacher is. It is needed to investigate more about the role of language proficiency to determine the teachers’ performance.